(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Financial markets play an important role in the economy, as it contributes to the financial and economic system of the state stability, as it reduces the adoption of the companies on the loans granted by the banks, as financial markets contribute to attracting and channeling savings to small savers who will be able to buy a number of shares proportional to their savings, It also provides them the place of exchange, and play technology and information systems an important role in facilitating exchanges and increased market activity, in this research touched on the importance of information technology in effect on the activity of the financial markets. Research is divided into three demands of the first concept of eating and the importance of technology and information systems and addressing the second requirement to identify the concept and importance of financial markets, while the third dealt with the requirement to the practical side of the search, and the search to find a set of conclusions and recommendations